FAKTOR-FAKTOR MEMPENGARUHI REMAJA MENGIKUTI KOMUNITAS MUSIK METAL DUNIA KAMI DUNIA HITAM KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Misriati "; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The presence of some teen love chart Sinembah against metal music they enjoy during the concert following the Underground Pekanbaru make them take the initiative to form metal music lovers is to form a community of music lovers in Chart Sinembah metal. The amount of the influence of friends or the environment to make the teens affected to participate in the community, because they feel they have common goals, according to some teenagers who are still in school they follow the community to entertain themselves by listening to rock music will give rise to a new spirit to re-learn back, consequently some other teenagers who become not had time to study because too often played with the community. The method used in this paper is a quantitative method that is a Analisia inferansial which gives a detailed description regarding a condition, symptom, the phenomenon, based on the fact that the author encountered in the field, after the data is processed and then described in terms of this study can be concluded kalimat.Hasil bahwasannya factors affecting teenagers included in the community more dominant through the encouragement of the self because most teenagers feel bahwasaanya they have in common that brings them together to fit into the community while adolescent relationships in the community shows to establish contact and interaction between members look good with still intertwining contact and interaction between members not only when they come together in the community alone but once outside the community.Keywords:Community,Youth,Music Metal